Editorial - Munga, Cosmas (Multidisciplinary Journal of Technical University of Mombasa, 2020)
Welcome to the 1st and Inaugural issue of the Multidisciplinary Journal of Technical University of Mombasa (MJTUM) December 2020 edition. A long awaited dream that has finally come true. MJTUM publishes multidisciplinary scholarly articles and offers a platform for academics and researchers to contribute to current knowledge in their respective disciplines. The publishing of this 1st and Inaugural issue is envisaged to motivate and inculcate the art of writing and publishing to both inexperienced and experienced writers. There is no formula on how to become a good writer but the only way is to start writing now and allow perfection to take its course with time. In this 1st and Inaugural issue, we have featured six articles in the form of reviews and full length research papers covering disciplines in computer science, medical science and electrical engineering that are quite exciting to read and to cite in other new works. These published papers in this maiden issue will definitely contribute to new knowledge as we expect more articles to be published in the subsequent near future issues of the journal. Once again, I welcome all of you to contribute articles to MJTUM that will undergo a professional publishing process in the shortest time possible.